Low-Dose Propranolol as Secondary Prophylaxis for Varix Bleeding Decreases Mortality and Rebleeding Rate in Patients with Tense Ascites - Jin Hwa Park (Journal of Clinical Medicine, 2019)
Background and Aim: The risk and benefit of non-selective propranolol in patients with tense ascites are controversial. This study aimed to investigate the effect of propranolol as secondary prophylaxis on varix rebleeding and overall mortality in patients with tense ascites. Methods: This study used a database of the Health Insurance Review and Assessment Service (HIRAS), which provides health insurance to 97.2% of the total population in Korea. A total of 80,071 patients first variceal bleeding as the first decompensated complication enrolled from 2007 to 2014. Results: There were 2274 patients with large-volume ascites prescribed propranolol as secondary prophylaxis after first varix bleeding. The average prescription dose of propranolol as secondary prophylaxis was 74 mg/day in patients with large-volume ascites. The mean duration of rebleeding was 22.8 months. Result of analysis showed that low-dose propranolol (40−120 mg/day) compared to inadequate propranolol dose (<40 mg/day) as secondary prophylaxis decreased overall mortality and varix rebleeding in patients with tense ascites. Conclusions: Low-dose propranolol (40−120 mg/day) as secondary prophylaxis for variceal re-bleeding decreased overall mortality and varix rebleeding recurrence in patients with tense ascites.